A cellular automation model of Eldana saccharina Walker infestation in sugarcane to improve the spatio-temporal planning of sugarcane planting and harvesting - De Wet, Pieter (Stellenbosch : Stellenbosch University, 2020)
Thesis (MCom)--Stellenbosch University, 2020.